Genetic testing in insurance: implications for non-EU insurance markets as a part of the European integration process - Arych, Mykhailo; Levon, Mariia; Arych, Halyna; Kulynych, Yurii (My University, 2021)
The purpose of the research study is to investigate the implications peculiarities of genetic testing in insurance for non-EU insurance markets as a part of the European integration process. The research model was developed by reviewing the previous studies in genetic testing in insurance. Also, it was applying the correlation-regression analysis for defining the relationship between the causes of death and life insurance market competitiveness in the context of genetic testing in insurance implications for non-EU insurance markets as a part of the European integration process. The originality of the study is explained by the fact that it was described the genetic testing in insurance implications for non-EU insurance markets as a part of the European integration process; secondly, for the first time was conducted the correlation-regression analysis of the interconnection of causes of death and life insurance market competitiveness (case study of Ukrainian insurance market) in the context of genetic testing in insurance implications for non-EU insurance markets as a part of the European integration process). The scientific value of the research results also is explained vie the possibility of applying these findings for start to regulate the using of the genetic testing for risk assessment at the Ukrainian life insurance market and in others European countries that are not members of the EU and in EU countries that do not have any specific regulations in applying genetic testing technologies for risk assessment in insurance.
Keywords: insurance; genetic testing; genetic discrimination; European Union; integration; human rights protection; cтрахування; генетичне тестування; генетична дискримінація; Європейський Союз; інтеграція; захист прав людини; кафедра фінансів